One of the manifestations of existentialism in the poetry of Salah Abdel-Sabour - Assistant Prof. Dr. Bushra Hanoun Mohsen (Thi Qar Arts Journal, 2021)
The one who is browsing modern Arabic poetry, must attract his attention to words that belong to the existential field more than others, such as: boredom, sadness, emptiness, loss ... etc. Sadness, anxiety, and estrangement highlight general existential themes in his poetry. Even the characters he employed in his texts are anxious, existential characters in general.The poet has tended to existential philosophizing, because of his sense of futility, anxiety and dark bitterness. Through the selected examples from the poetic achievement of Salah Abdel-Sabour, we will show the reader the face of existentialism, its ideas and propositions. Existentialism in the poetry of Salah Abdel-Sabour is nothing but one of the stages of his poetic development, which are intertwined stages between them